Addressing problematic consumption: an action research experience from the Social Network Analysis - Vera, Juan José; Barroso, Nicolás (AWARI, 2020)
This paper is classified under the trend of studies that make use of ‘Social Network Analysis’ (SNA) to serve as guidelines for social intervention. Within the field of SNA, work has been carried out based on what is referred to as the socio-centric approach, with the aim of revealing a type of complete network, the Subjective Communities Networks, which are built from Community Treatment Groups pertaining to the Argentine Office of Drug-related Comprehensive Policies (SEDRONAR for its Spanish acronym) in order to address problematic abuse in socially vulnerable backgrounds. These groups belong to the ECO2 model, which was devised to intervene in a wide range of social suffering phenomena, and uses the SNA as a theoretical and methodological viewpoint for assessing people and communities. This thought is an attempt to answer the following question: how does SNA help formulate social intervention strategies for SEDRONAR groups in the Province of Mendoza?